Dynamic and Static Pilot Plant Scale Supercritical CO2 Extraction of Brucea Javanica Seed: Towards Zero Waste Biorefinery - Cheah, Siang Aun (Curtin University, 2023)
This study addresses the increased demand for health products amid the COVID-19 pandemic by proposing supercritical CO2 (Sc-CO2) extraction as an environmentally friendly alternative to Soxhlet extraction for Brucea javanica oil (BJO). Optimal Sc-CO2 conditions yielded comparable oil (17.6%) with superior antioxidant activity. Additionally, utilizing Brucea javanica seed waste for enzymatic hydrolysis demonstrated potential value-added products. Life cycle assessment favored Sc-CO2 extraction, emphasizing its sustainability for BJO extraction and promoting a circular biorefinery approach.